2011
DOI: 10.1590/s1806-83242011000400010
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of two daily use mouthrinses: randomized clinical trial using an experimental gingivitis model

Abstract: Two antimicrobial agents, a fixed combination of essential oils (EOs) and 0.07% cetylpyridinium chloride (CPC) are found in commercially available mouthrinses, Listerine  Antiseptic and Crest  Pro Health  , respectively. Both mouthrinses have been shown to control dental plaque and gingivitis in short and longer term studies. The aim of this study was to determine the comparative effectiveness of these two mouthrinses using a 2-week experimental gingivitis model. Qualified subjects were randomly assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
2
10
0
1
Order By: Relevance
“…The reduction in amount of plaque found to be statistically significant (p=0.000) well corroborates with the results obtained in the previous studies carried out by Loe [18], and Lang et al [19], and Sharma et al also found significant amount of plaque reduction in the children who used 0.2% chlorhexidine mouthwash [20]. Chlorhexidine has an excellent antiplaque activity and substantivity property [21]. Haq et al [22,23] reported that Cetylpyridinium chloride mouthwash in combination According to an in vitro comparative study on the evaluation of the efficacy of chlorhexidine and a herbal mouthwash on dental plaque, 20 plaque samples were collected from periodontitis patients, and healthy patients were streaked on blood agar.…”
Section: Discussionsupporting
confidence: 88%
“…The reduction in amount of plaque found to be statistically significant (p=0.000) well corroborates with the results obtained in the previous studies carried out by Loe [18], and Lang et al [19], and Sharma et al also found significant amount of plaque reduction in the children who used 0.2% chlorhexidine mouthwash [20]. Chlorhexidine has an excellent antiplaque activity and substantivity property [21]. Haq et al [22,23] reported that Cetylpyridinium chloride mouthwash in combination According to an in vitro comparative study on the evaluation of the efficacy of chlorhexidine and a herbal mouthwash on dental plaque, 20 plaque samples were collected from periodontitis patients, and healthy patients were streaked on blood agar.…”
Section: Discussionsupporting
confidence: 88%
“…The screening of titles and abstracts initially identified 25 full‐text articles. Fifteen papers were excluded because the alcohol‐containing control rinse had a low hydro‐alcohol concentration of 0.02% or 5% , and in one study, the concentration of the hydro‐alcohol was not provided . In addition, in one study, the control rinse was either a chlorhexidine or sanguinarine rinse , and in two another, a water‐based control was used .…”
Section: Resultsmentioning
confidence: 99%
“…EO demonstrated significant reduction in MGI (9.4%), PI (6.6%) and BI (29%) compared to CPC. EO presented clinical superiority compared to CPC in the short-term management of plaque and gingivitis [38].…”
Section: Commercial Agents and Biofilm/mentioning
confidence: 97%